Proteomic Analyses Of Streblus Asper Root Extract On Cervical Cancer - Roslan, Muhammad Nabil Fikri (2022)
Cervical cancer is the third most prevalent cancer in women. Despite recent advances in cancer treatment, there were 569,847 incidents and 311,365 deaths worldwide in 2018. The current treatment options such as radiotherapy and chemotherapy have been typically found to cause adverse side effects that hinder the treatment efficacy. In contrast, natural products have been found to provide better treatment efficacy. Therefore, this study was conducted to explore the potential of one natural product known as Streblus asper root extract to be an alternative prospect to the current treatment practise.